Factors Affecting the Human Development Index in Central Sulawesi 2017-2022 - Giska Putri; Santi Yunus; Yunus Sading; Failur Rahman; Andi Herman Jaya (ProBisnis : Jurnal Manajemen, 2024)
This research aims to determine the influence of GRDP, Average Years of Schooling, and Life Expectancy on Central Sulawesi's Human Development Index (HDI). This research examines 6 years from 2017-2022 data, with 13 districts/cities. The analysis technique used is panel data regression analysis. The tool used to carry out testing is Eviews 9. The tests used in this research are the CEM, FEM, REM, Chow, Hausman, and Lagrange Multiplier (LM) tests. The research results show that (1) GRDP has a negative and significant effect on HDI, (2) Average Years of Schooling has a negative and significant effect on HDI (3) Life Expectancy has a positive and significant effect on HDI. The research results show that the GRDP variables, Average Years of Schooling, and Life Expectancy influence the Human Development Index in Central Sulawesi Province in 2017 -2022.